Wildlife professionals' and graduate students' perceptions regarding scientific publishing - Lauren A. Hernandez‐Rubio; Richard M. Kaminski; Christopher K. Williams (Wildlife Society Bulletin, 2023)
Abstract Within academia and research, publishing peer‐reviewed articles is expected for dissemination of knowledge and is used as a measure of professional performance. However, few papers have been published on professionals' and graduate students' perceptions of student publication performance, how professionals encourage student publishing, and what types of publication barriers exist for graduate students to publish. In 2019, we emailed a survey to professional and student attendees of the 2013 and 2016 North American Duck symposia as a representative cadre of waterfowl and wildlife biologists. We surveyed 469 professionals and 98 students who attended the symposia. Response rates were 42% and 45% for professionals and students, respectively, and deemed reliable as response rates approached 50%. Fifty percent and 69% of professional respondents indicated they felt frustration motivating their Ph.D. and M.S. students to publish, respectively. Of strategies used to motivate graduate student publishing, 79% of students ranked providing congenial encouragement most effective, while 60% of professionals ranked playing a major role in drafting and editing as most effective. Both professionals and students considered lack of time during and outside work hours as barriers to publishing graduate work. Professionals and students agreed that asking students to sign a contract at time of their initial matriculation may be an effective strategy to publish. Information from this study adds to knowledge on graduate student publishing practices and can be used to improve methods to increase graduate student publication rates in wildlife science and conservation. Similar surveys can be conducted face‐to‐face or remotely at international wildlife and other ecological conferences to broaden application of our results. We encourage students to generate publications from their research by writing separate thesis/dissertation chapters to expedite the publication process.